EFFICACY OF NICOTINAMIDE MONONUCLEOTIDE SUPPLEMENTATION (NMN) IN BLOOD NICOTINAMIDE ADENINE DINUCLEOTIDE (NAD) FOR ANTI-AGING IN ADULTS: A SYSTEMATIC REVIEW - Asrithari Dewi, Made Yudha; Dananjaya, I Made Dwi; Saraswati Dewi Permadi, Anak Agung Sagung; Sigmahadewi, Risma Nopara (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Aging is a risk factor for various chronic diseases such as diabetes, dyslipidemia, metabolic, neurological, and cardiovascular disease, and other age-related disorders. Nicotinamide mononucleotide (NMN) is one of the endogenous intermediate molecules in nicotinamide adenine dinucleotide (NAD) biosynthesis, and its biological function is known to be related to an increase in NAD concentration. NAD levels decline and are critical for human health and longevity. The material and methods using a systematic review of RCT, with participants of healthy adults aged between 20-65 years old, agreed to take NMN supplementation compared to Placebo. The inclusion criteria are RCT studies regarding NMN administration with an outcome to prevent aging using primary objective measurement of blood nicotinamide adenine dinucleotide (NAD) concentration. Trial quality was assessed using the JBI checklist. We included six studies with an average duration of intervention between 10-12 weeks with a dosage of NMN 250-900mg/day. All six studies showed that NMN supplementation can significantly improve blood NAD concentration and cause only mild adverse effects during the trial. In conclusion, NMN supplementation has a significant clinical impact in preventing adult aging.